(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
Rastko Petrović’s last manuscripts, related to his work on a historical novel about the Renaissance, are kept at the Endowment of Ljubica Luković, home to the Rastko and Nadežda Petrović Collection. The preserved synopsis is of special importance as it reveals the author’s creative idea and poetic assumptions. The author’s oeuvre is marked by a continued interest in the Renaissance, which is central to the last phase of his creative work as an émigré in the USA. The examination of the manuscript and synopsis reveals Petrović’s thoughts on the Renaissance as he endeavoured to become an American author.